Lack of functional alpha-lactalbumin prevents involution in Cape fur seals and identifies the protein as an apoptotic milk factor in mammary gland involution - Lefèvre Christophe; Sharp Julie A; Nicholas Kevin R (BMC Biology, 2008)
Abstract Background The mammary gland undergoes a sophisticated programme of developmental changes during pregnancy/lactation. However, little is known about processes involving initiation of apoptosis at involution following weaning. We used fur seals as models to study the molecular process of involution as these animals display a unique mammary gland phenotype. Fur seals have long lactation periods whereby mothers cycle between secreting copious quantities of milk for 2 to 3 days suckling pups on land, with trips to sea alone to forage for up to 23 days during which time mammary glands remain active without initiating apoptosis/involution. Results We show the molecular basis by which alpha-lactalbumin (LALBA), a secreted milk protein, is absent in Cape fur seals and demonstrate an apoptotic function for LALBA when exposed to mammary cells. Conclusion We propose that apoptosis does not occur in fur seal mammary glands due to lack of LALBA in fur seal milk, allowing evasion of involution during a foraging trip. Our work identifies LALBA as a milk factor that feeds back on the mammary gland to regulate involution.